Housing design practice and energy efficiency consideration in Nigeria - Abdul Majid, Noor Hanita; Hussaini, Ibrahim Udale (2011)
The growing concern on the reduction of energy consumption in the residential sector of national economies rests on some parameters and issues that deserve to be resolved. Fundamental among these issues are the architectural concern, the appliances/ services efficiency issue: and most recently the human behavioral dimension. This study focuses on the architectural issue with the objective of determining the level of energy efficiency consideration in housing design practice by the housing stakeholders in Nigeria, with a notion that arousing the professional cultures of the stakeholders, particularly architects and building services engineers in the directions of efficiency can help improve energy efficiency design practice. This is in recognition of the fact that more than one third of the world’s energy is used in buildings: and a majority in houses and apartments (Wulfinghoff, 2003) [1]. Therefore, instituting energy efficiency design practice would lead to attainment of significant reduction in household energy consumption. This study employs opinion survey on the stakeholders (architects, building services engineers and builders) as a measure of their perception and practice in our attempt to evolve energy efficiency housing design practice guidelines. The result reveals an obvious gap in housing design practice and energy efficiency consideration in Nigeria.